KAJIAN INFRASTRUKTUR DAN PEMELIHARAAN TERMINAL YOUTEFA, KOTA JAYAPURA - Maay, George; Rante, Harmonis; Rusim, Dewi Ana (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2023)
Transportation is a derivative need that arises due to demand for commodities that differ from one region to another. Transportation is formed by several components including infrastructure and people. Therefore, at travel meeting points between one region and another, a place that can guarantee smooth transfers, namely the terminal, is needed. Youtefa Terminal is one of the terminals in Jayapura City. The location of the Youtefa Terminal is integrated with the Youtefa Market so that the existence of the Youtefa Terminal is very important for the community. The research location is Youtefa Terminal. The analytical method used is a qualitative method. The results showed that the existing infrastructure at Youtefa Terminal, such as the parking area, passenger waiting room and terminal office, was in very poor condition. So in order to optimize the condition of the Youtefa Terminal, it is necessary to develop a Service Strategy and Infrastructure Maintenance in the Youtefa Terminal.